Dissecting the genomic regions, candidate genes and pathwaysusing multi-locus genome-wide association study for stem rotdisease resistance in groundnut - Veerendrakumar, H. V.; Sudini, Hari Kishan; Kiranmayee, Bangaru; Devika, Talwar; Gangurde, Sunil S.; Vasanthi, R. P.; Kumar, Nirmal A. R.; Bera, Sandip K.; Guo, Baozhu; Liao, Boshou; Varshney, Rajeev K.; Pandey, Manish K. (Wiley, 2025)
Stem rot, caused by Sclerotium rolfsii Sacc., is a devastating soil-borne disease causing up to 80% yield losses in groundnut globally. To dissect the genetic basis of resistance, we evaluated a diverse minicore germplasm panel over 3 years in stem rot sick-field conditions. Multi-locus genome-wide association study with the 58K single nucleotide polymorphisms (SNPs) Axiom_Arachis array genotyping identified 13 significant genomic regions associated with resistance across eight chromosomes with logarithm of the odds (LOD) scores ranging from 4.5 to 12.4 and R2 values between 6.9% and 58%. Within these regions, 145 candidate genes were implicated, including wall-associated receptor kinases, lucine-rich repeat and NB-ARC domain proteins, and peroxidase superfamily proteins. These genes orchestrate resistance through pathogen perception (e.g., receptor-like kinases), direct inhibition (R genes), toxin detoxification, and activation of transcription factors driving protective compound synthesis for cell recovery. If these defenses are compromised, a hypersensitive response-mediated apoptosis is triggered. Notably, resistance was exclusive to Virginia-type groundnut. The identified candidate genes showed strong correlation with RNA-seq data from stem rot-infected plants, reinforcing their role in the transcriptional defense response. Three kompetitive allele-specific PCR markers, namely, SnpAH00614 (on auxin-related gene AhSR001), SnpAH00625 (on histidine triad protein gene AhSR002), and SnpAH00626 (on E3 ubiquitin ligase gene AhSR003), were validated, confirming their significant contribution to stem rot resistance. These markers may facilitate the development of stem rot-resistant varieties through direct application in breeding programs through marker-assisted selection.